Local radicality and survival outcome of pancreatic cancer surgery - Niesen, Willem; Hank, Thomas; Büchler, Markus W.; Strobel, Oliver (Annals of gastroenterological surgery, 2019)
Pancreatic cancer remains a therapeutic challenge. Surgical resection in combination with systemic chemotherapy is the only option promising long-term survival and potential cure. However, only about 20% of patients are diagnosed with tumors that are still in a resectable stage. Even after potentially curative resection and modern regimens for adjuvant chemotherapy, the majority of patients develop local and systemic recurrence resulting in median overall survival times of 28-54 months. The predominance of systemic recurrence and its impact on survival may lead to the assumption that surgical radicality and local control play only minor roles in the treatment of pancreatic cancer. This review provides an overview of the recent literature on surgical radicality and survival outcome in pancreatic cancer. The current evidence on the extent of lymphadenectomy, the prognostic impact of the extent of lymph node involvement, and the impact of the resection margin status on postresection survival are reviewed. Data from recent studies performed in the context of modern surgery and adjuvant therapy provide good evidence of a considerable impact of local radicality on survival after pancreatic cancer surgery. Surgical techniques that have been developed to refine oncological resections and to increase local control as well as resectability are highlighted. These techniques include artery-first approaches, level-3 dissection with removal of the periarterial nerve plexus, the triangle operation, and extended resections. Local radicality and quality of surgical resection remain among the most important parameters that determine the chances for survival in patients with non-metastatic pancreatic cancer.
Gesehen am 13.11.2020